Hepatic Energy Metabolism and the Differential Protective Effects of Sevoflurane and Isoflurane Anesthesia in a Rat Hepatic Ischemia-Reperfusion Injury Model - Nurdan Bedirli; Ebru Ofluoğlu; Mustafa Kerem; Gülten Ütebey; Murat Alper; Demet Yılmazer; Abdülkadir Bedirli; Onur Özlü; Hatîce Paşaoğlu (2008)
In Brief BACKGROUND: We investigated the effects of isoflurane and sevoflurane in a warm liver ischemia-reperfusion (IR) model on cytokines, hepatic tissue blood flow (HTBF), energy content, and liver structure. METHODS: Seventy-two Wistar rats were randomly assigned into 1 of 3 groups: Control group, no volatile anesthetics; sevoflurane group, 2% sevoflurane; isoflurane group, 1.5% isoflurane. Thirty minutes after the start of volatile anesthetics, rats were subjected to 45 min hepatic ischemia and 2 and 4 h of reperfusion. Rats were killed at the end of ischemia, 2 and 4 h of reperfusion. Aspartate aminotransferase and alanine aminotransferase, HTBF, malondialdehyde, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, energy charge, and histologic examination were used to evaluate the extent of liver injury. RESULTS: Serum alanine aminotransferase and aspartate aminotransferase levels were similar in control and isoflurane groups while there was a significant decrease in the sevoflurane group in the postischemic period (P < 0.01). HTBF was remarkably better in the sevoflurane group than in the isoflurane group and worse in the control group. Tissue malondialdehyde levels were significantly low in the sevoflurane group compared with the isoflurane group at 2 h of reperfusion (P < 0.05) and reached its maximum value in the postischemic period in the control group. After ischemia, 2 and 4 h of reperfusion, tumor necrosis factor-α and interleukin-1β values were lowest in the sevoflurane group and highest in the control group but it was not statistically significant (P > 0.05). In the sevoflurane group, hepatic adenosine triphosphate and energy charge were significantly high at all measurement times. At the postischemic period, energy charge was lower compared with the sevoflurane and isoflurane groups. The degree of hepatocyte injury was small in the sevoflurane group. CONCLUSIONS: Clinically relevant concentrations of sevoflurane given before, during, and after hepatic ischemia protected the liver against IR injury, whereas the effects of isoflurane on hepatic IR injury were not notable. IMPLICATIONS: Ischemia-reperfusion injury to the liver can lead to changes in blood flow, cytokine energy content, and liver structure. This study, performed in a rat hepatic injury model, demonstrates that sevoflurane, but not isoflurane, protects against such injury.